Using gait analysis’ parameters to classify Parkinsonism: A data mining approach - Ricciardi, Carlo; Amboni, Marianna; De Santis, Chiara; Improta, Giovanni; Volpe, Giampiero; Iuppariello, Luigi; Ricciardelli, Gianluca; D'Addio, Giovanni; Vitale, Carmine; Barone, Paolo; Cesarelli, Mario (Computer methods and programs in biomedicine, 2019)
•Acquisition of gait analysis for patients affected by PD and PSP.•Extraction of spatial and temporal parameters for each patient.•Implementation of ensembles of trees (Random forests and gradient boosted Tree) to distinguish typical and atypical forms of parkinson. Parkinson's disease (PD) is the second most common neurodegenerative disorder in the world, while Progressive Supranuclear Palsy (PSP) is an atypical Parkinsonism resembling PD, especially in early stage. Assumed that gait dysfunctions represent a major motor symptom for both pathologies, gait analysis can provide clinicians with subclinical information reflecting subtle differences between these diseases. In this scenario, data mining can be exploited in order to differentiate PD patients at different stages of the disease course and PSP using all the variables acquired through gait analysis. A cohort of 46 subjects (divided into three groups) affected by PD patients at different stages and PSP patients was acquired through gait analysis and spatial and temporal parameters were analysed. Synthetic Minority Over-sampling Technique was used to balance our imbalanced dataset and cross-validation was applied to provide different training and testing sets. Then, Random Forests and Gradient Boosted Trees were implemented. Accuracy, error, precision, recall, specificity and sensitivity were computed for each group and for both algorithms, including 16 features. Random Forests obtained the highest accuracy (86.4%) but also specificity and sensitivity were particularly high, overcoming the 90% for PSP group. The novelty of the study is the use of a data mining approach on the spatial and temporal parameters of gait analysis in order to classify patients affected by typical (PD) and atypical Parkinsonism (PSP) based on gait patterns. This application would be helpful for clinicians to distinguish PSP from PD at early stage, when the differential diagnosis is particularly challenging.